Role of BMP-7 on biological parameters osseointegration of dental implants: Preliminary results of a preclinical study - López-Valverde, Nansi; Aragoneses, Javier; López-Valverde, Antonio; Rodríguez, Cinthia; Aragoneses, Juan Manuel (Frontiers in Bioengineering and Biotechnology, 2023)
The aim of this work was to analyze and compare the effect of bone morphogenetic protein-7 on biological parameters related to implant osseointegration in an experimental animal model. Sixteen dental implants were placed in the tibias of four randomly selected minipigs for the following dental implant surface treatments: Group A: conventional treatment of the dental implant surface by SLA (n = 8) and Group B: treatment of the dental implant surface with carboxyethylphosphonic acid and bone morphogenetic protein-7 (n = 8). The animals were sacrificed one month after dental implants placement and a histomorphometric study was performed for the evaluation of bone-to-implant contact, corrected bone-to-implant contact, new bone formation, interthread bone density and peri-implant density using Student's t-test and the nonparametric Mann-Whitney test. The histomorphometric parameters bone-to-implant contact and corrected bone-to-implant contact showed statistically significant differences between the study groups; 34.00 ± 9.92% and 50.02 ± 10.94%, respectively (p = 0.004) for SLA and 43.08 ± 10.76% and 63.30 ± 11.30%, respectively (p = 0.003) for BMP-7. The parameters new bone formation, interthread bone density and peri-implant density did not show statistically significant differences between the study groups (p = 0.951, p = 0.967 and p = 0.894, respectively). Dental implant surfaces treated with carboxyethylphosphonic acid and BMP-7 improve the biological response of dental implants to osseointegration.